Pembinaan Wanita Perimenopause Melalui Program Sehat dan Bugar (SEGAR): Development of Perimenopausal Women Through the Healthy and Fit Program (SEGAR) - Susani Hayati; Busyra Hanim; Linda Suryani; Dona Martilova; Rena Afri Ningsih; Dewwiny Septa Dale; Ingelia Ingelia (IKATAN ALUMNI DOSEN MAGANG KEMENRISTEKDIKTI TAHUN ANGKATAN 2017, 2024)
Perimenopause is a natural transition period towards menopause. This period occurs within 2 to 8 years starting at the age of 40-55 years. Menstruation begins to become irregular, characterized by shortened or lengthened menstrual cycles. Many factors can influence early menopause, including smoking habits, a family history of early menopause, chemotherapy treatment for cancer, hysterectomy, removal of ovaries and psychological factors from continuous stress. The aim of this community service is to improve the quality of perimenopausal women's health through a healthy and fit (SEGAR) program. This program begins with 3 stages: the first stage is providing education through counseling, the second stage is health screening through checking blood pressure, blood glucose, cholesterol and uric acid and the third stage is carrying out healthy exercise. The results of outreach activities show an increase in knowledge of perimenopausal women pre and post test.